The effects of differences in water exchange on the productivity of glass eel stage in Anguilla bicolor bicolor culture - Setiadi Eri (EDP Sciences, 2021)
Eel, Anguilla bicolor bicolor has an economic value for export commodity. Eel farming has been developed both of home to industries scales. However, the main problem during the glass eel culture is the low survival rate, characterized by high mortality. This condition is related to the culture technique that has not been established yet, especially water quality management. The research aims to determine the best water exchange during the culture of the glass eel on the survival, growth, and blood glucose. The different percentages of water exchange as a treatment were followed A) control (without water exchange); B) 20% of water exchange; C) 40% of water exchange; and D) 60% of water exchange. The water exchange has affected the survival, growth, and blood glucose (P<0.05). The ammonia, nitrite, and nitrate values during the culture period showed that the control was higher compared to the others. The water exchange of 40% is suitable for glass eel stage culture to obtain the best survival and growth.